Respon Pemberian Ekoenzim Terhadap Pertumbuhan dan produksi Beberapa Varietas Jagung Manis (Zea Mays L. Saccharata Sturt) - Hulu, Henrikus Sabarudin; Luta, Devi Andriani; Harahap, Ariani Syahfitri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aimed to determine the effect of ecoenzyme administration on the growth and yield of several sweet corn varieties. The study used a factorial randomized block design (RBD) consisting of two factors with nine treatment combinations and three replications, resulting in 27 experimental units. The first factor was the ecoenzyme dosage, which consisted of three levels: 0 ml/plot, 10 ml/plot, and 20 ml/plot. The second factor was the sweet corn varieties: Bonanza f1, Super sweet, and RS-8. The results showed that ecoenzyme administration affected plant height, number of leaves, stem diameter, number of fruits, fruit diameter, cob weight, and cob length, but had no significant effect on fruit weight. Varietal treatment showed significant and insignificant effects on plant height, number of leaves, stem diameter, number of fruits, fruit weight, fruit diameter, cob weight, and cob length.